Analisis Kebutuhan Sumber Daya Manusia Pemerintahan Desa Kesugihan Kecamatan Pulung, Kabupaten Ponorogo - Yusuf Adam Hilman; Redi Lutvian Alfrianto; Tatik Rohmawati (Jurnal Ilmu Pemerintahan, 2024)
This study was conducted with the aim of analyzing the needs of government human resources in Sugihan Village, Pulung District, Ponorogo Regency based on Regulation and Law Number 6 of 2014. This type of research uses descriptive qualittaif, where all data is obtained from the results of interviews and documents in the village Sugihan. To obtain the validity of researchers' data using triangulation tests. In this study, the results of the study are known that the most ages that are village officials are 45-55, while the highest level of village apparatus education is high school graduates. From the results of the interview of Sugihan Village apparatus there is no self -development in increasing the competencies of the local government or from the sub -district level, there is limited human resources due to lack of participating in training or capacity building. This can be seen from the community development in Kesugihan Village which has not met the criteria in accordance with the law in terms of social development due to the lack of basic training that is followed and given by village officials. Therefore Sugihan Village must conduct training for village officials to create a device that can develop Sugihan Village.